Approaching the end: a theological exploration of death and dying - Jones, David Albert (Oxford studies in theological ethics, 2007)
David Albert Jones focuses upon the writings on death of four outstanding Christian thinkers, Ambrose of Milan, St Augustine Thomas Aquinas, and Karl Rahner. His study is relevant to the current euthanasia debate, but also considers broader issues such as how to should act in the face of death's approach